Effectiveness of Coping Through Audio Visual Education of J. Watson's Caring Concept Model on Reducing Anxiety Pre Percutaneous Coronary Intervention (PCI) of Cad Patients in the Hospital - Endah Tri Rahayuningrum; Tri Ismu Pujianto; Rusnoto Rusnoto (GLOBAL HEALTH SCIENCE GROUP, 2025)
Coronary Heart Disease (CHD) is the leading cause of death globally, including in Indonesia. One of the procedures to treat CHD is Percutaneous Coronary Intervention (PCI), but this action often causes significant anxiety in patients. Unmanaged anxiety can worsen the physical and mental condition of patients. This study aims to analyze the effectiveness of audio-visual education based on the Caring Jean Watson concept in reducing anxiety in pre-PCI patients at Dr. Loekmonohadi Hospital, Kudus. The study design was a quasi-experiment with a